Australian Adolescents’ Experiences of Aggression and Abuse by Intimate Partners - Daff, Elizabeth S. (Journal of interpersonal violence, 2021)
International research has shown that intimate partner abuse affects many young people throughout adolescence. Despite a recent focus on family and intimate partner violence in Australia, there is almost no Australian data on the frequency or nature of youth intimate partner abuse (YIPA). The current study sought to better understand the frequency and nature of YIPA in Australian adolescents. To this end, 423 participants aged between 14 and 18 from Victorian (Australian) high schools completed an anonymous questionnaire regarding experiences of perpetration and victimization in their most difficult intimate relationship. Results showed high rates of both YIPA victimization and perpetration among boys and girls who had been in intimate relationships. As was expected, verbally and psychologically aggressive behaviors were reported more frequently than physically or sexually aggressive actions. Mutual YIPA was detected more frequently than unidirectional YIPA, and most commonly involved high severity reciprocal aggression. The current study further confirmed that YIPA is a complex and heterogeneous issue, involving a range of behaviors, patterns of use, and severities. A gender-sensitive approach to the current study allowed for consideration of the similarities and differences between male and female experiences of YIPA. The current study provides a novel method of ascertaining both the frequency and severity of YIPA experiences in a sample of young people, expands on both Australian and international literature, and identifies important gender considerations for future research.